Dual protection: A tydeoid mite effectively controls both a problem pest and a key pathogen in tomato. Issue 1 (7th October 2021) - Pijnakker, Juliette; Moerkens, Rob; Vangansbeke, Dominiek; Duarte, Marcus; Bellinkx, Stijn; Benavente, Alfredo; Merckx, Jonas; Stevens, Ian; Wäckers, Felix
Abstract: BACKGROUND: The tomato russet mite (TRM), Aculops lycopersici, and powdery mildew (PM), Oidium neolycopersici, are two major problems in tomato cultivation for which no effective biocontrol solutions exist to date. In a greenhouse compartment, we investigated the potential of preventatively establishing the iolinid omnivorous mite Pronematus ubiquitus on potted tomato plants to control both pest and pathogen simultaneously. RESULTS: Using Typha pollen, P. ubiquitus established well on tomato plants, with numbers reaching up to 250 motiles per tomato leaflet. The built‐up population was capable of controlling subsequent infestations with both TRM and PM. This represents the first report of an arthropod protecting a crop against pests as well as disease. CONCLUSION: The implementation of P. ubiquitus in tomato crops could be a real game‐changer as it eliminates the need for repeated pesticide use or sulphur applications. The finding that arthropods can effectively control diseases opens up new opportunities for biological crop protection. © 2021 Society of Chemical Industry. Abstract : The tomato russet mite (TRM), Aculops lycopersici, and powdery mildew (PM), Oidium neolycopersici, are two major problems in tomato cultivation. Using field trials, we here demonstrate that the iolinid omnivorous mite Pronematus ubiquitus is highly effective in controlling both pest and pathogen simultaneously.